Beginning game development with Amazon Lumberyard : create 3D games using Amazon Lumberyard and Lua - Herman, Jaken Chandler (Apress, 2019)
Create stunning 3D games in a short amount of time using Amazon Lumberyard, a free and exciting game development platform. This book is a ground-up, out-of-the-box tutorial on 3D game development and programming with Lua and Amazon Lumberyard with little or no game development experience required. Beginning Game Development with Amazon Lumberyard walks you through the user interface of the Amazon Lumberyard engine; teaches you how to develop detailed terrain using heightmaps, megatextures, weather, and vegetation; and takes you through exporting the game for distribution. The book will show you how to create a player as well as enemies while not getting bogged down with third-party tools for animation or model creation. You will also work with simple physics, colliders, meshes, weather generation, Lua scripting, user interface development, and much more. By the end of the book, you will be able to create many different types of video games using the Amazon Lumberyard engine and even have a completed project ready to release or put in your portfolio. You will: Discover the mechanics and terminology of game development Familiarize yourself with the Amazon Lumberyard game engine in detail Modify game scripts using the Lua language Discover how to optimally structure game layers.